Evaluation of the Covid 19 Vaccine Policy for the Elderly Community in Pekanbaru City - Isril, Isril; Harirah MS, Zulfa; Rizaldi, Annas (Faculty of Social and Political Science Universitas Brawijaya, 2021)
The number of Covid-19 cases in Indonesia is still high. One of the efforts made by the government is vaccination. As one of the cities with high enough Covid-19 cases, Pekanbaru City has also implemented a vaccination policy. One of the priority targets for vaccination in Pekanbaru City is the Elderly Community. However, the reality is that many older people still have not received the vaccination according to the target set. This study aims to determine the factors that influence the implementation of vaccination for the elderly and to see further how the relationship between the Central Government and Local Government in the implementation of vaccination policy.Â This study uses a qualitative method by collecting data from informants and various documents. The data obtained were then analyzed using a predetermined theory.Â The results of this study, the number of elderly who received the vaccine decreased in stage II. Factors that become obstacles in the implementation of vaccination for the elderly such as body conditions are not recommended and the lack of public confidence in the quality of vaccines. Public distrust will affect the success of a policy. Thus, clear information is needed regarding the safety of vaccination for the elderly.